Pharmacokinetics and bioequivalence study of valacyclovir hydrochloride capsules after single dose administration in healthy Chinese male volunteers - Lin, Hui; Tian, Yuan; Tian, Ji-Xin; Zhang, Zun-jian; Mao, Guo-Guang (Arzneimittelforschung, 2010)
The aim of the present study was to compare the bioavailability of valacyclovir (CAS 124832-26-4; INN: valaciclovir) from two valacyclovir hydrochloride (CAS 214832-27-5) capsules (150 mg/capsule as test preparation and 150 mg/capsule commercially available original capsule of the drug as reference preparation) in 20 Chinese healthy male volunteers, aged between 20 and 27. The study was conducted according to an open, randomized, single blind, 2-way crossover study design with a washout phase of 7 days. Blood samples for pharmacokinetic profiling were taken up to 24 h post-dose. Valacyclovir hydrochloride is rapidly converted to acyclovir (CAS 59277-89-3) after oral administration, so the pharmacokinetics and bioequivalence of valacyclovir hydrochloride can be studied by determining the plasma concentration of acyclovir. Plasma concentrations of acyclovir were determined with a validated liquid chromatographytandem mass spectrometry (LC-MS/MS) method. The pharmacokinetic parameters of test and reference formulations were estimated as follows: the maximum plasma concentrations (Cmax) were 2.04 ± 0.43 μg/mL and 2.01 ± 0.50 μg/mL; the median Tmax were 1.1 ± 0.3 h and 1.0 ± 0.3 h; plasma elimination half-lives (t1/2) were 2.94 ± 0.42 h and 2.85 ± 0.28 h. Values of AUC0–t demonstrate nearly identical bioavailability of valacyclovir hydrochloride from the examined formulations. AUC0–15 were 6.70 ± 1.26 μg · h/mL and 6.96 ± 1.25 μg · h/mL. Areas under the plasma concentration-time curve (AUC0–∞ were 6.90 ± 1.30 μg · h/mL and 7.15 ± 1.31 μg · h/mL. Both primary target parameters, AUC0–∞ and AUC0–t were tested parametrically by analysis of variance (ANOVA) and relative bioavailabilities were 96.69 ± 7.89% for AUC0–∞, 96.40 ±8.0% for AUC0–15. Bioequivalence between test and reference preparation was demonstrated for both parameters, AUC0–∞ and AUC0–t. The 90% confidence intervals of the T/R-ratios of logarithmically transformed data were in the generally accepted range of 80–125%. It meant that the test formulation was bioequivalent to the reference formulation for valacyclovir hydrochloride.
Keywords: Acyclovir; Antiviral drugs; CAS 59277-89-3; CAS 124832-26-4; CAS 214832-27-5; Valacyclovir; Valacyclovir hydrochloride, bioequivalence, pharmacokinetics